The nursing service needs of old adults in long term care facilities: current status and associated factors - Haiyan Wu; Peier Lu; Chaoer Wu; Xia Liu (BMC Health Services Research)
Abstract Background Long term care facilities, as an integral part of the current social nursing service system, bear the important function of providing nursing services for the older adults. This study conducts an in-depth analysis of the nursing service needs of the older adults, to offer a scientific basis for the improvement of nursing services in long term care facilities. MethodsD A questionnaire survey was conducted among the older adults of 24 long term care facilities in Hangzhou, China from March 1 to June 30, 2024. The needs scale of older adults nursing service was used for survey. Bivariate and multivariable linear regression analyses were performed to identify factors associated with nursing service needs in long-term care facilities. Results The study sample comprised 1,242 older adults from long-term care facilities. The mean total score for nursing service needs was 162.15 ± 14.38, suggesting a relatively high demand for nursing services among older adults in these facilities. Multivariable regression analysis identified age, self-care ability, educational level, and average monthly income as significant factors associated with nursing service needs (all p < 0.05). Conclusion The nursing service needs of older adults in long-term care facilities are substantial and influenced by a range of factors. Healthcare providers and long-term care facilities should develop and implement targeted interventions to effectively address these needs.